2021
DOI: 10.1002/nme.6814
|View full text |Cite
|
Sign up to set email alerts
|

Topologically optimal design and failure prediction using conditional generative adversarial networks

Abstract: Among the various structural optimization tools, topology optimization is the widely used technique in obtaining the initial design of structural components. The resulting topologically optimal initial design will be the input for subsequent structural optimizations such as shape, size and layout optimizations. However, iterative solvers used in conventional topology optimization schemes are known to be computationally expensive, thus act as a bottleneck in the manufacturing process. In this paper, a novel dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The results showed that increasing the resolution led to improved prediction accuracy, as indicated by the correlation values presented in table 1. This agrees with similar models from the literature [72,73] in which higher resolution led to increased accuracy. Figure 15 shows the training and testing loss of the three models trained with different resolutions.…”
Section: Effect Of Model Resolutionsupporting
confidence: 92%
“…The results showed that increasing the resolution led to improved prediction accuracy, as indicated by the correlation values presented in table 1. This agrees with similar models from the literature [72,73] in which higher resolution led to increased accuracy. Figure 15 shows the training and testing loss of the three models trained with different resolutions.…”
Section: Effect Of Model Resolutionsupporting
confidence: 92%
“…These optimal designs are derived after the systematic processing through one or more of the topology, size, shape, and layout optimisations. 60 The primary motivation for choosing this problem lies in the expected geometric nonlinear behaviour of the optimal structure due to its relative slenderness. The accurate CGPR prediction of the force-displacement behaviour of the optimal structure is crucial for design purposes as optimisation algorithms are generally expensive.…”
Section: Example 02: Stiffening Response Of Topologically Optimal Des...mentioning
confidence: 99%
“…Structural optimisation of components and assemblies has gained increasing popularity due to the high stiffness‐to‐weight ratio of the optimal design. These optimal designs are derived after the systematic processing through one or more of the topology, size, shape, and layout optimisations 60 . The primary motivation for choosing this problem lies in the expected geometric nonlinear behaviour of the optimal structure due to its relative slenderness.…”
Section: Nonlinear Responses Of Materials Systemsmentioning
confidence: 99%
“…For instance, in Reference 20, the boundary conditions, loading conditions, volume fraction and domain size are directly encoded into the input tensor of a U‐Net autoencoder (AE) architecture that is exploited to predict the corresponding optimal topology. An alternative solution was proposed in Reference 21, through the combined use of CNNs and conditional generative adversarial networks, which can generate the optimal design and trace the corresponding von Mises (VM) stress contour, eventually allowing the identification of the most stressed regions.…”
Section: Introductionmentioning
confidence: 99%